(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
One of the most pressing problems in education in Latvia today is to prepare specialists to participate in the labour market and become specialists who respect and ensure occupational safety for those working in the national economy. The study analysed the aspects of cognitive ergonomics for students in the framework of the professional practice of “Motor tools”. Working with a chainsaw can create dangerous situations, significantly endangering a person’s health or even life, as well as affecting his or her working capacity. The well-being of the employee significantly affects the quality and performance of work, because cognitive aspects – fatigue, stress - affect a person’s working capacity. Different methods were used to evaluate the impact of cognitive ergonomics on students’ work abilities: a survey, key indicator method (A, B and C), the method of determining the psychological climate, the method of work ability index, quick exposure check method, expert interviews, as well as the NASA-TLX method. Kendall correlation coefficient calculation methods were used. Work abilities were analysed at the beginning and end of the internship for both full-time and part-time students. The results of the study show that during professional practice students have an increased workload, as well as a significantly increased physical load, causing overload to be possible for individuals with normal physical fitness. Fatigue and reduced performance appear at the end of the practice, especially when it was necessary to make decisions about action in emergency situations. Based on the consensus of experts as characterized by the Kendall correlation coefficient, (p < 0.05) cognitive aspects significantly affect a safe work environment, negatively affecting work productivity and human performance, and response to emergency situations. Currently, due to physical unpreparedness, students often face ergonomic overload caused by a lack of experience and knowledge of work safety, which manifests itself in physical fatigue. Instructors need to pay more attention and point out incorrect or non-ergonomic actions and movements in order to promote a more balanced and safer work environment. As well, students themselves need to pay more attention to their work performance.